Onomastic Analysis of Arab Proper Names: Identity Category, Origin, and Quranic Presence - Fatima El Zahraa; Fatimaezzahraa El Assali (UIN Sunan Gunung Djati Bandung, 2025)
Accurate identification of the gender of Arab personal names is crucial for proper grammatical and cultural usage. Observing first-semester Arabic Education students using al-‘Arabiyyah Bayna Yadayk (Vol. 1, dars 56, wahdah 7), the name 'Ilham' was treated as male. However, the textbook lists it as female, affecting feminine markers. The study aimed to analyze Arab personal names to determine their gender classification, origin, and Quranic linkage. Three approaches were applied to 30 Arab proper names, selected on the assumption that 15 were male and 15 were female, using dictionary consultation, computational tools (namsor.app and genderize.io), and social media searches. Each name was examined to verify gender, determine its linguistic or geographical origin (Arabic or non-Arabic), and identify its occurrences in the Quran. Based on the three approaches, the overall gender distribution of the names was 40.83% male, 48.33% female, and 10.83% gender-neutral. Most names (93%) were Arabic, with 7% non-Arabic. The origins were predominantly Middle Eastern, with limited representation from other regions. Approximately one-third (33.33%) were mentioned in the Quran. Among the 30 names analyzed, 23 were clearly gendered (10 male, 13 female), 1 was neutral or mutual, and six showed variation across sources. The study showed that naming practices among Arabs reflect identity, social belonging, and cultural continuity. The findings may benefit educators, translators, students, and researchers, although the small dataset and preliminary classification criteria limit them.